Single-Cell Transcriptome Profiling Reveals the Suppressive Role of Retinal Neurons in Microglia Activation Under Diabetes Mellitus - Xiao, Yuhua; Hu, Xing; Fan, Shuxin; Zhong, Jiawei; Mo, Xinzhi; Liu, Xialin; Hu, Youjin (Frontiers in Cell and Developmental Biology, 2021)
Diabetic retinopathy, as one of the common complications of diabetes mellitus, is the leading cause of blindness in the working-age population worldwide. The disease is characterized by damage to retinal vasculature, which is associated with the activation of retina microglial and induces chronic neurodegeneration. Previous studies have identified the effects of activated microglial on the retinal neurons, but the cellular and molecular mechanisms underlying microglial activation is largely unknown. Here, we performed scRNA-seq on the retina of non-human primates with diabetes mellitus, and identified cell-type-specific molecular changes of the six major cell types. By identifying the ligand-receptor expression patterns among different cells, we established the interactome of the whole retina. The data showed that TNF-α signal mediated the activation of microglia through an autocrine manner. And we found TGFβ2, which was upregulated in cone dramatically by hyperglycemia, inhibited microglia activation at the early stage of diabetic retinopathy. In summary, our study is the first to profile cell-specific molecular changes and the cell-cell interactome of retina under diabetes mellitus, paving a way to dissect the cellular and molecular mechanisms underlying early-stage diabetic retinopathy.